Genetic characterisation of invasive breast cancer: a comparison of CGH and PCR based multiplex microsatellite analysis. Issue 11 (1st November 2001) - Buerger, H; Schmidt, H; Beckmann, A; Zänker, K S; Boecker, W; Brandt, B
Abstract : Aims —Comparative genomic hybridisation (CGH) is a reliable tool to gain an overview of all unbalanced chromosomal alterations within a tumour. Nevertheless, the high numbers of tumour cells required and the comparatively low resolution are drawbacks of this technique. Polymerase chain reaction (PCR) based multiplex microsatellite analysis represents a semi-automated, highly reproducible method, which requires small amounts of tumour cells. This is a comparative study of CGH and microsatellite analysis. Methods —Eighty one samples of invasive breast cancer were investigated by two sensitive multiplex PCRs containing three microsatellites each of six markers (D6S261, D11S907, D6S300, D11S927, D8S272, and D11S925), and two additional microsatellite markers located within intron 1 of the epidermal growth factor recepter gene (egfr) and p53 (p53CA). Results —At least one example of loss of heterozygosity was detectable in all breast cancer tissues. However, the overall rate of accordance between the two methods tested was only 61%. An increasing rate of the number of genetic alterations in each case was mirrored by a constantly increasing fractional allelic loss index. Conclusions —PCR based multiplex microsatellite analysis using this panel of eight microsatellite markers not only enables the characterisation of cells that have malignant potential in a high frequency of patients with breast cancer, but can also give an estimate of the degree of genetic progression.